PERSEPSI ANGGOTA LEGISLATIF LAKI-LAKI TERHADAP PENGARUSUTAMAAN GENDER DI DPRD PROVINSI BALI PERIODE 2014-2019 - Ifa Ristanty, Ni Luh Komang; Bandiyah, Bandiyah; Erviantono, Tedi (Jurnal Nawala Politika, 2017)
Perception of male legislative members towards gender mainstreaming in Bali Provincial DPRD Period 2014-2019 used the theory of female existentialism, Simone de Beauvoir. The method used is a sequential explanatory design by cencus sampling technique. The findings if this study, firstly: variable x it was found rejection if female legislators become leaders with 73% percentage, because female legislators are considered not wise. Second; variable y it was found that male legislators considered women legislators to have performed in the legislative functions properly and seriously. Third; the patriarchal culture in Bali is not a problem of the lack of women who plunge in the legislative institution, but the strategy of women in showing their existence. Based from the data, author found that the strategy of gender mainstreaming had been work well in parlement and need to improved in legislative function so thet the whole concept of gender mainstreaming can work effectively in the council of Bali Province for the period 2014-2019. Keywords: perception, gender mainstreaming, members of the legislature